Intelligent ISFET sensory system for water quality monitoring - Chen, Deyu (2009)
This thesis presents a new intelligent ISFET sensory system dedicated to a precision pH sensory function as well as long-term monitoring capability without being jeopardized by temperature and drift fluctuations in the water-quality monitoring environment. The research leads to the information of a new ISFET behavior-SPICE model for ISFET sensor simulation, a new non-saturation based ISFET interface circuit, a new saturation-based ISFET interface circuit, a novel ISFET nonlinear temperature compensation method, a novel ISFET drift and slow pH response compensation method, a new dynamic current mirror for use in temperature compensation and a microcontroller-based ISFET sensory system that realizes the proposed temperature and drift compensation technique for precision pH sensing in long-term monitoring at different temperatures. The ISFET interface circuit has been fabricated in TSMC CMOS 0.25 µm process technology. The Si3N4-gate ISFET sensor is based on the D+T Microelectrónica, A.I.E (CNM), Spain. The proposed intelligent ISFET sensory system, including the sensor, interface IC, microcontroller and support circuits, has been validated by the experiments at a single 3.3V supply. It exhibits a maximum accuracy error of 0.02 pH at 23oC and 0.05 pH at 40oC with dual compensation. The compensation results show a maximum time drift of 0.003 pH/hour (0.166 mV/hour) at 23oC and an average temperature drift of 0.00049 pH/hour/oC (0.0245 mV/hour/ oC) for a reference temperature increase from 23oC to 40oC, with the value of the pH solution ranging from 4 to 9 in six-hourly measurements. These measured results outperform those of the reported drift reduction techniques, suggesting that the ISFET sensory system using novel compensation is able to provide significant immunity against temperature change, time drift and temperature drift, which are favorable towards robust measurements in environmental monitoring applications.